Memahami Kekeluargaan Sebagai Budaya Organisasi di Indonesia - Mulya, Teguh Wijaya; Rahayu, Yusti Probowati; Mawardi, Artiawati (ANIMA Indonesian Psychological Journal, 2006)
Kekeluargaan (close to the term of "kinship") has often been stated as a culture immensely representing Indonesia. However kekeluargaan has not had a clear definition, especially in relation with organizational culture. The method of data collection implemented on twelve informants in this qualitative research was interview and observation. results from this study found that there are three essential funtions of kekeluargaan, which were the function of affection, the function of maintenance, and the funtion of empowerment. The assumptions underlining the culture of kekeluargaan were the importance of socialization, the equality of humankind, and the workers as the company's assets. The impact of kekeluargaan is that the workers felt belongingness to the company, and at the end increasing productivity. The implementation of kekeluargaan culture must deliberately take into account the context of the local culture in order to achieve the organizational effectiveness. Kekeluargaan sering dinyatakan sebagai budaya yang kental terasa di Indonesia, namun belum ada definisi yang jelas mengenai apa sebenarnya kekeluargaan itu, terutama dalam kaitannya dengan budaya organisasi. Metode pengumpulan data pada dua belas informan dalam penelitian kualitatif ini adalah wawancara dan observasi. Ditemukan adanya tiga fungsi yang menjadi esensi budaya kekeluargaan, yaitu : fungsi afeksi, pemeliharaan, dan pemberdayaan. Asumsi bahwa sosialisasi adalah hal yang penting, semua manusia adalah setara, dan pekerja sebagai aset perusahaan menjadi asumsi yang mendasari budaya kekeluargaan. Dampaknya, pekerja merasa memiliki perusahaan sehingga produktivitas meningkat. Penerapan kekeluargaan dalam organisasi perlu memperhatikan konteks budaya setempat agar dapat mencapai efektivitas organisasi.